Innovative Analyses Support a Role for DNA Damage and an Aberrant Cell Cycle in Myelodysplastic Syndrome Pathogenesis. (7th June 2011) - Head, David R.; Jacobberger, James W.; Mosse, Claudio; Jagasia, Madan; Dupont, William; Goodman, Stacey; Flye, Leanne; Shinar, Andrew; McClintock-Treep, Sara; Stelzer, Greg; Briggs, Robert; Shults, Keith
Abstract : We used flow cytometry to analyze the cell cycle, DNA damage, and apoptosis in hematopoietic subsets in MDS marrow. Subsets were assigned using CD45, side scatter, CD34, and CD71. Cell cycle fractions were analyzed using DRAQ 5 (DNA content) and MPM-2 (mitoses). DNA damage was assessed using p-H2A.X, and apoptosis using Annexin V. Compared to controls, MDS patients demonstrated no increased mitoses in erythroid, myeloid, or CD34+ cells. Myeloid progenitors demonstrated increased G2 cells, which with no increased mitoses suggested delayed passage through G2. Myeloid progenitors demonstrated increased p-H2A.X, consistent with DNA damage causing this delay. Annexin V reactivity was equivalent in MDS and controls. Results for each parameter varied among hematopoietic compartments, demonstrating the need to analyze compartments separately. Our results suggest that peripheral cytopenias in MDS are due to delayed cell cycle passage of marrow progenitors and that this delayed passage and leukemic progression derive from excessive DNA damage.